Dioxin exposure associated with fecundability and infertility in mothers and daughters of Seveso, Italy. Issue 3 (26th December 2020) - Eskenazi, Brenda; Ames, Jennifer; Rauch, Stephen; Signorini, Stefano; Brambilla, Paolo; Mocarelli, Paolo; Siracusa, Claudia; Holland, Nina; Warner, Marcella
Abstract: STUDY QUESTION: Is there an association between 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) exposure and fecundability and infertility among Seveso women and their daughters? SUMMARY ANSWER: TCDD exposure is associated with a decrease in fecundability and increased risk of infertility in women, as well as their daughters. WHAT IS KNOWN ALREADY: In animal studies, maternal exposure to TCDD is associated with decreased fertility in offspring. Effects of TCDD are mediated by activation of the aryl hydrocarbon receptor (AHR) pathway. STUDY DESIGN, SIZE, DURATION: The Seveso Women's Health Study (SWHS) has followed 981 women exposed to TCDD in a 1976 accident since 1996. In 2014, we initiated the Seveso Second Generation Study to follow-up their children. PARTICIPANTS/MATERIALS, SETTING, METHODS: We obtained information on pregnancy history including time of trying to conceive from SWHS women and their daughters who were 18 years or older. We considered TCDD exposure as initial 1976 serum TCDD concentration and estimated TCDD at pregnancy. We examined relationships of TCDD exposure with time to pregnancy (TTP, the monthly probability of conception within the first 12 months of trying) and infertility (≥12 months of trying to conceive). We also assessed contributions of polymorphisms in the AHR pathway via genetic risk score. MAIN RESULTS AND THE ROLE OF CHANCE: Among SWHS women (n = 446), median TTP was 3 months and 18% reported taking ≥12 months to conceive. Initial 1976 TCDD (log10 ) was associated with longer TTP (adjusted fecundability odds ratio = 0.82; 95% CI 0.68–0.98) and increased risk of infertility (adjusted relative risk = 1.35; 95% CI 1.01–1.79). TCDD at pregnancy yielded similar associations. Among SWHS daughters (n = 66), median TTP was 2 months and 11% reported taking ≥12 months to conceive. Daughters showed similar, but non-significant, associations with maternal TCDD exposure. LIMITATIONS, REASONS FOR CAUTION: A limitation of this study is time to pregnancy was reported retrospectively, although previous studies have found women are able to recall time to conception with a high degree of accuracy many years after the fact. The number of SWHS daughters who had a live birth was small and we were unable to examine fecundability of SWHS sons. WIDER IMPLICATIONS OF THE FINDINGS: Consistent with previous findings in animal studies, our study found that TCDD exposure may be associated with decreased fertility in Seveso mothers and potentially in their daughters exposed in utero . There may be susceptible genetic subgroups. The literature has largely considered the genetics of the AHR pathway in the context of male fertility but not female fertility, despite strong biological plausibility. These findings should be replicated in larger populations and of different ancestry. Future studies in Seveso should examine the sons and the grandchildren of exposed mothers given the animal literature suggesting potential heritable epigenetic effects. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by grant numbers F06 TW02075-01 from the National Institutes of Health, R01 ES07171 and 2P30-ESO01896-17 from the National Institute of Environmental Health Sciences, R82471 from the U.S. Environmental Protection Agency and #2896 from Regione Lombardia and Fondazione Lombardia Ambiente, Milan, Italy. J.A. was supported by F31ES026488 from the National Institutes of Health. The authors declare they have no actual or potential competing financial interests. TRIAL REGISTRATION NUMBER: N/A.